2014
DOI: 10.1002/chem.201304870
|View full text |Cite
|
Sign up to set email alerts
|

Carbene‐9‐BBN Ring Expansions as a Route to Intramolecular Frustrated Lewis Pairs for CO2 Reduction

Abstract: Reactions of phosphine-derived carbenes with 9-borabicyclo[3.3.1]nonane (9-BBN) result in ring-expansion reactions to generate novel intramolecular frustrated Lewis pairs (FLPs). These FLPs effect the catalytic reduction of CO2 in the presence of boranes to give BOB and methoxy-borate species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(92 citation statements)
references
References 52 publications
5
83
0
4
Order By: Relevance
“…Rivard reported the first example of boron hydride insertion into NHCs, which has been followed by a number of observations of analogous boron hydride reactivity . As of yet, there are no reports of analogous reactivity for the heavier group 13 elements.…”
Section: Resultsmentioning
confidence: 99%
“…Rivard reported the first example of boron hydride insertion into NHCs, which has been followed by a number of observations of analogous boron hydride reactivity . As of yet, there are no reports of analogous reactivity for the heavier group 13 elements.…”
Section: Resultsmentioning
confidence: 99%
“…In a related study, Piers and coworkers 146 150 In closely related work, we reported the use of C 3 H 2 (NPR 2 ) 2 BC 8 H 14 (Scheme 19) as a catalyst which was derived from the insertion of C 3 H 2 (NPR 2 ) 2 into 9-BBN. 151 In a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 further study, we 152 showed that hydroboration of CO 2 by 9-BBN is catalyzed by phosphine, affording a mixture of MeOB(C 8 H 14 ) and O(B(C 8 H 14 )) 2 in 98% yield with as little as 0.02% phosphine as the catalyst.…”
Section: Scheme 18 Stoichiometric Reductions Of Co 2 With P/al Flpsmentioning
confidence: 97%
“…1 Despite NHCs being considered to be robust spectator ligands in catalysis, the activation of C-N bonds has significant generality, being thus far observed for the elements Be, 2 B, [3][4][5] Si, 6 Ni, 7 and Zn. 1 Despite NHCs being considered to be robust spectator ligands in catalysis, the activation of C-N bonds has significant generality, being thus far observed for the elements Be, 2 B, [3][4][5] Si, 6 Ni, 7 and Zn.…”
Section: Introductionmentioning
confidence: 99%